Combinatory in vitro effects of the β2-agonists salbutamol and formoterol in skeletal muscle cells. (1st April 2023) - Piribauer, M.; Jiang, L.; Kostov, T.; Parr, M.; Steidel, S.; Bizjak, D.A.; Steinacker, J.M.; Diel, P.
Abstract: β2-agonists are used for the treatment of bronchoconstriction, but also abused in doping. Beside an ergogenic activity β2-agonists may have also anabolic activity. Therefore, we investigated the anabolic activity and associated molecular mechanisms of Salbutamol (SAL) and Formoterol (FOR) alone, as well as in combination in C2C12 myotubes. In differentiated C2C12 cells, dose-dependent effects of SAL and FOR (alone/in combination) on myotube diameter, myosin heavy chain (MHC) protein expression and the mRNA expression of genes involved in hypertrophy were analyzed. β2-adrenoceptor 2 (ADRB2), androgen receptor (AR) and estrogen receptor (ER) inhibitors, as well as dexamethasone (Dexa) were co-incubated with the β2-agonists and myotube diameter was determined. SAL and FOR treatment significantly induced hypertrophy and increased MHC expression and the mRNA expression of Igf1, mTOR, PIk3r1 and AMpKa2. In contrast to an ER inhibitor, the ADRB2 and AR inhibitors, as well as Dexa antagonized FOR and SAL induced hypertrophy. Combined treatment with SAL and FOR resulted in significant additive effects on myotube diameter and MHC expression. Future clinical studies are needed to prove this effect in humans and to evaluate this finding with respect to antidoping regulations. Graphical Abstract: ga1 Highlights: SAL and FOR treatment significantly induced hypertrophy of C2c12 myotubes. SAL and FOR treatment increased MHC expression in C2C12 myotubes. mTOR signaling is involved in SAL and FOR mediated hypertrophy. SAL and FOR induced hypertrophy are mediated by the β2-adrenoceptor 2 and the androgen receptor. Combined treatment with SAL and FOR resulted in significant additive effects on hypertrophy and MHC expression.